2011
DOI: 10.1007/s13142-010-0011-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes from a multiple-risk-factor diabetes trial for Latinas: ¡Viva Bien!

Abstract: Latinas with type 2 diabetes are in need of culturally sensitive interventions to make recommended longterm lifestyle changes and reduce heart disease risk. To test the longer-term (24-month) effects of a previously successful, culturally adapted, multiple-healthbehavior- change program, ¡Viva Bien!, 280 Latinas were randomly assigned to usual care or ¡Viva Bien!. Treatment included group meetings to promote a culturally adapted Mediterranean diet, physical activity, supportive resources, problem solving, stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
136
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(145 citation statements)
references
References 68 publications
2
136
1
Order By: Relevance
“…33,49,50,54,55 While we did find that all participants had improvements in A1C at 3 months, this improvement was not sustained at 6 months. Participants may not have maintained the skills they gained after the weekly contact ended.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…33,49,50,54,55 While we did find that all participants had improvements in A1C at 3 months, this improvement was not sustained at 6 months. Participants may not have maintained the skills they gained after the weekly contact ended.…”
Section: Discussioncontrasting
confidence: 54%
“…While some studies have demonstrated no improvements in diabetes outcomes using a lay leader approach, 33,49,50,[54][55][56] several other studies have noted that trained peers can effectively lead self-management education interventions in community settings and improve clinical outcomes. 13,19,20,[22][23][24]26,27,[57][58][59][60] Studies with Mexican Americans with diabetes utilizing peer-led diabetes self-management interventions have found improvements in glucose control.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this important reduction, DSME has a positive effect on other clinical, psychosocial, and behavioral aspects of diabetes. DSME/S is reported to reduce the onset and/or advancement of diabetes complications (21,22), to improve quality of life (19,(23)(24)(25)(26) and lifestyle behaviors such as having a more healthful eating pattern and engaging in regular physical activity (27), to enhance self-efficacy and empowerment (28), to increase healthy coping (29), and to decrease the presence of diabetes-related distress (16,30) and depression (31,32). These improvements clearly reaffirm the importance and value-added benefit of DSME.…”
mentioning
confidence: 99%
“…They are available in different formats, including individual and group-based interventions conducted in hospitals, medical homes or other care organisations, as well as IT based (e.g., web-based or phone-based programmes) (Powers et al, 2015). DSME programmes have been shown to produce positive effects on clinical, psychological and behavioral outcomes in diabetic patients, including improved glycaemic control (Brunisholz et al, 2014;Ellis et al, 2004;Steinsbekk, Rygg, Lisulo, Rise and Fretheim, 2012;Weaver et al, 2014), improved quality of life (Cochran and Conn, 2008;Powers et al, 2015;Tang, Funnell and Oh, 2012;Thorpe et al, 2013), increased diabetes knowledge (Steinsbekk et al, 2012) healthier lifestyle behaviours (Tang et al, 2012;Toobert et al, 2011), more healthy coping (Thorpe et al, 2013) and enhanced self-efficacy (Steinsbekk et al, 2012;Tang et al, 2012).…”
mentioning
confidence: 99%